2020
DOI: 10.1155/2020/6782659
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Venous Disease Patients Showed Altered Expression of IGF‐1/PAPP‐A/STC‐2 Axis in the Vein Wall

Abstract: Chronic venous disease (CVeD) has a remarkable prevalence, with an estimated annual incidence of 2%. It has been demonstrated how the loss of homeostatic mechanisms in the vein wall can take part in the physiopathology of CVeD. In this regard, it has been described how different axis, such as IGF-1/PAPP-A/STC-2 axis, may play an essential role in tissue homeostasis. The aim of this research is to study both genetic and protein expressions of the IGF-1/PAPP-A/STC-2 axis in CVeD patients. It is a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…This evidence supports the importance of IGF-1/IGF-1R in the pathogenesis of CVeD. 30 IRS-4 may also negatively regulate the expression of other IRS-family proteins via competitive inhibition. 31 , 32 Thus, IRS-4 hyperactivation could be a downstream effect of IGF-1/IGF-1R binding that occurs in the venous wall of CVeD patients.…”
Section: Discussionsupporting
confidence: 78%
“…This evidence supports the importance of IGF-1/IGF-1R in the pathogenesis of CVeD. 30 IRS-4 may also negatively regulate the expression of other IRS-family proteins via competitive inhibition. 31 , 32 Thus, IRS-4 hyperactivation could be a downstream effect of IGF-1/IGF-1R binding that occurs in the venous wall of CVeD patients.…”
Section: Discussionsupporting
confidence: 78%
“…In this sense, significant changes in peptide growth factors and their receptors have been identified in the venous wall of patients with CVD, including acidic fibroblast growth factor (aFGF), VEGF, and insulin-like growth factor 1 (IGF-1), and its receptor (IGF-1R) [ 198 ]. The last route appears to be particularly important in the venous wall of patients with CVD, where we have recently reported an altered homeostatic IGF-1/PAPPA/STC-2 axis [ 199 ]. TGF-β1 has also been related to the pathophysiology of CVD.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Panagiotou et al showed increased PAPP-A and STC-2 by exercise in healthy individuals [ 35 ]. Ortega et al demonstrated increased PAPP-A and decreased STC-2 gene expression in patients with chronic venous disease [ 36 ]. Hjortebjerg et al revealed unchanged PAPP-A and but decreased STC-2 expression after Roux-en-Y gastric bypass operation in obese subjects [ 37 ].…”
Section: Resultsmentioning
confidence: 99%